Human dietary and internal exposure to zearalenone based on a 24-hour duplicate diet and following morning urine study - Zhang, Shuo; Zhou, Shuang; Gong, Yun Yun; Zhao, Yunfeng; Wu, Yongning (Environment international, 2020)
•ZEN exposure study incorporated duplicate diet and biomonitoring in same subjects.•Dietary and internal exposures were significantly correlated, both far below the TDI.•Mean PDI was 1.6 times higher than mean EDI; possible causes were discussed.•Wheat contributed most to ZEN exposure; maize was most heavily contaminated.•Possible differences in ZEN excretion capabilities and patterns among populations. Zearalenone is a widespread mycotoxin with high estrogenic activity. This study aimed to characterize the exposure of ZEN in a Chinese population during harvest season in 2016. Exposure to ZEN was measured using both duplicate diet method and human biomonitoring approaches. Duplicate diet samples from 199 individuals (4–80 years old) and their following morning urine samples were collected and analyzed using LC-MS/MS methods sensitive for ZEN, ZAN, α/β-ZEL and α/β-ZAL. ZEN was detected in 59.8% of the food samples at a mean level of 1.21 ± 2.15 μg/kg. The estimated daily intake (EDI) of ZEN was calculated from food contamination and consumption data at a mean level of 25.6 ± 38.6 ng/kg bw/day, representing 10.2% of the tolerable daily intake (TDI) set by EFSA and 5.1% of the provisional maximum tolerable daily intake (PMTDI) set by JECFA, respectively. Wheat appears to be the main diet source of ZEN exposure, contributing over 80% of the mean EDI. Children had the highest EDI at 37.5 ± 56.3 ng/kg bw/day (p < 0.05). Urine samples were analyzed both before and after enzymatic hydrolysis to determine the free and total amounts of ZEN biomarkers. The majority of ZEN was excreted as conjugates with the mean fZEN/tBM ratio of 25.4%. Adolescents had the highest excretion of ZEN biomarkers among all age groups (p < 0.05). Probable daily intake (PDI) was calculated from ZEN biomarkers and an excretion rate of 36.8%, giving a mean value of 41.6 ± 65.5 ng/kg bw/day. Significant correlation between internal and external exposure measurement was evidenced in this study (r = 0.344, p < 0.01). Although the mean PDI was approximately 1.6 times the mean EDI, these two approaches resulted in similar calculated degrees of ZEN exposure, both markedly below the health-based guidance value. This study is the first to compare ZEN exposure in a same population based on both diet study and human biomonitoring approaches. Significant differences of PDI/EDI ratios were found in different age groups (p < 0.05), possibly indicative of diversified excretion capabilities and metabolism patterns within the population.